1994
DOI: 10.1007/bf01676880
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting leakage following esophageal anastomosis

Abstract: Esophageal anastomotic leaks remain the most serious problem following extirpative procedures for esophageal carcinoma. We conducted a retrospective analysis of 352 patients with carcinoma in the thoracic esophagus who had undergone esophageal anastomosis following esophagectomy at the Kurume University Hospital between 1981 and 1990. Of these, 94 patients (27%) developed anastomotic leaks, and out of this subgroup, 21 (6%) died as a direct result of the leak. A further 20 patients (6%) underwent repair of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
45
1
4

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 13 publications
3
45
1
4
Order By: Relevance
“…In our study, more than half of the radiological leaks were asymptomatic. Several authors have reported similar observations [10][11][12] .…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In our study, more than half of the radiological leaks were asymptomatic. Several authors have reported similar observations [10][11][12] .…”
Section: Discussionsupporting
confidence: 68%
“…The patients were kept non per os until a second GS study, and then were allowed oral feeding even if the second GS still showed a contained leak and remained asymptomatic. Zieren et al [10] , Tilanus et al [11] and Lee et al [12] , in their series, also observed that radiological leaks remained asympto matic.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…В сериях ранних сообщений, относящихся к 1990-м годам, частота не-состоятельности пищеводного анастомоза после га-стрэктомии и проксимальной резекции желудка до-стигала 30 % [2]. Публикации последних лет показывают отчетливую положительную динамику снижения частоты несостоятельности анастомоза, что является отражением безусловного прогресса хирур-гической техники и усовершенствования инструмен-тария.…”
Section: Introductionunclassified
“…1) stellen eine häufige (10–30%) und gefürchtete (Mortalität 11–35%) Komplikation nach Ösophagusresektionen dar [1,2,3,4]. Der Unterdruck im Thorax begünstigt, dass infizierte Sekrete in der Speiseröhre durch die Leckage in das Mediastinum gelangen und in der Folge eine Mediastinitis verursachen können.…”
Section: Introductionunclassified